PENGARUH MODEL PEMBELAJARAN OUTDOOR LEARNING BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI KEANEKARAGAMAN HAYATI DI MA WAHID HASYIM BALUNG TAHUN AJARAN 2025/2026 - Safira Faradila; Abdillah Fatkhul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of the Outdoor Learning model based on Education for Sustainable Development (ESD) on students' science process skills in biodiversity learning at MA Wahid Hasyim Balung. The study was motivated by the low level of students' science process skills due to the dominance of conventional teaching methods and the underutilization of the surrounding environment as a learning resource. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of an experimental class that received Outdoor Learning based on ESD and a control class that received conventional instruction. Data were collected through observation, tests, interviews, and documentation and analyzed using descriptive statistics, the Mann–Whitney test, and N-Gain analysis. The results showed that the implementation of the learning model was categorized as very good, with an implementation percentage of 87%. The Mann–Whitney test produced an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a significant effect of the Outdoor Learning model based on ESD on students' science process skills. Furthermore, the average N-Gain score of the experimental class (87.09) was higher than that of the control class (72.00). Therefore, it can be concluded that the Outdoor Learning model based on Education for Sustainable Development (ESD) is more effective than conventional learning in improving students' science process skills in biodiversity learning.